One-factor-at-a-time-guided development of simvastatin-loaded alginate-chitosan microspheres - Carlos, Sophia Isabelle R.
Pursuant to the concept of quality by design, recent trends in polymer-based drug delivery system research utilize design of experiments (DOE) to systematically identify factor levels that yield optimal responses. One-factor-at-a-time (OFAT) guided experiments remain useful in providing a basis for these DOE studies, particularly for the low and high levels of the factors they can use for optimization. This study employed this approach to fabricate microspheres loaded with simvastatin (SMV) in attempt to address the bioavailability issues of the drug brought by its premature metabolism in the gastrointestinal tract. SMV concentration (Factor 1), polymer (ALG:CS) ratio (Factor 2), and crosslinker (CaCl2) concentration (Factor 3) were evaluated individually in terms of their effect on particle size, encapsulation efficiency (%EE), and loading capacity (%LC). Initial assessments were performed with three levels, followed by the addition of other levels necessary for further analysis. All three factors showed parabolic effects in relation to %EE and %LC. For particle size, Factor 1 and 3 generally showed a linear relationship with indications of plateauing. Factor 2 demonstrated a curved trend, though it is not conclusive of a parabolic effect. In consideration of these observations supported by statistical analyses, the study proposed low and high values of these factors which can be used for studies aiming to optimize the formulation.